Arbitrage Money - Haykov, Joseph Mark (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
Arbitrage Money Theory (AMT) introduces a novel perspective on the fundamental nature of money, challenging the conventional view that primarily identifies it as a medium of exchange. We posit that the intrinsic function of money is as a unit of account. This pivotal role facilitates the comparison of subjective costs and benefits. First, money is used to measure not only the prices we pay to obtain benefits from trade, but also costs of obtaining these benefits, for our wages too are measured in money. Moreover, money is instrumental in preventing arbitrage—a form of market inefficiency. From this primary role, money’s secondary functions as a medium of exchange and a store of value naturally emerge. Our theory contends that recognizing money's primary function as a unit of account allows for the creation of theoretical models that more accurately reflect its operation in real-world economies. This perspective diverges from traditional models that largely focus on money's role as a medium of exchange—an assumption that, while generally valid, does not always encompass the complexities of economic realities. AMT aims to bridge this gap, offering a more comprehensive understanding of money's multifaceted roles in the economic system.